THE PRACTICE OF VOTE BUYING AND ITS IMPACTS ON ELECTIONS (CIPEEX, 2025)
Vote buying, a persistent phenomenon in democracies like Brazil, represents a serious threat to electoral integrity and popular sovereignty. This practice distorts the will of the electorate, compromises the legitimacy of electoral results, and perpetuates cycles of corruption and poor governance, undermining political representation and trust in democratic institutions. The objective of this expanded summary was to discuss the limitations of Law No. 9,840/99 and explain its role in combating vote buying. The methodology used was analytical and descriptive research, with qualitative data collection through scientific articles and relevant publications on the topic, focusing on the definition, impact, and fight against vote buying, as well as the origin, role, and challenges of the aforementioned law. In response to popular pressure, Law Nº. 9,840/99 emerged as an important milestone, being the first of popular initiative to combat vote buying, strengthening protection mechanisms against the abuse of economic power and facilitating the revocation of mandates. However, its effectiveness is limited by difficulties in oversight, complexity in obtaining evidence, judicial delays, and a political culture that still tolerates clientelism. The persistence of this practice in many regions indicates that effective combat depends not only on strict laws but also on their efficient application by the justice system and continued social mobilization to promote behavioral and institutional changes.
Keywords: Vote buying; Law Nº. 9,840/1999; Democracy